Զուգահեռներ հույների տեղահանությունների ու կոտորածների և Հայոց ցեղասպանության միջև (1913–1923 թթ.) - Գևորգ Վարդանյան (ՀՀ ԳԱԱ հրատ.)
В 1913–1923 гг. в Турции были организованы и проведены массовые депортации и резня греческого и армянского населения. С точки зрения исследования Геноцида армян важное значение имеет его сравнение с депортацией и резней греков. Это позволяет не только увидеть основные различия и сходства, но и помогает более глубоко понять национальную политику Османской империи. From 1913 to 1923 in Turkey were organized and carried out the mass deportations and massacres of the Armenian and Greek population. In term of the study of the Armenian Genocide it is important to compare it with the deportations and massacres of the Greeks. This allows us not only to see the main differences and similarities, but also helps better understand the national policy of the Ottoman Empire.
Keywords: History; Armenian Genocide (1915); D History; AMS Armenian Massacres